Mesoparasitic copepods (Copepoda: Cyclopoida) associated with polychaete worms in European seas - Boxshall, Geoff A.; O’reilly, Myles; Sikorski, Andrey; Summerfield, Rebecca (Zootaxa, 2019)
A large collection of mesoparasitic copepods from polychaete hosts collected in northern European waters was examined. The term mesoparasitic refers to highly transformed copepods where the adult female attaches by embedding part of its body in the host. Representatives of five known familes were found and a new family is established. A single new species, Bradophila minuta sp. nov., was described in the family Bradophilidae. It occurred exclusively on the flabelligerid Diplocirus glaucus (Malmgren, 1867). Two genera of the family Herpyllobiidae were represented: Herpyllobius Steenstrup & Lütken, 1861 and Eurysilenium M. Sars, 1870. Herpyllobius arcticus Steenstrup & Lütken, 1861 was found on at least five different polynoid hosts, two of which, Harmothoe fragilis Moore, 1910 and Antinoe sp., were new host records. A new species, H. cluthensis sp. nov. was described from Malmgrenia species in Scottish waters. The large species, Herpyllobius cordiformis Lützen, 1964, was collected in Arctic waters from Eunoe cf. oerstedi. It is the first report of this parasite in Europe. The common parasite H. polynoes (Krøyer, 1864) was found on six different polynoid hosts, three of which, Harmothoe bifera, Malmgreniella mcintoshi Tebble & Chambers, 1982 and Eunoe ?barbata are new host records. Eurysilenium truncatum M. Sars, 1870 was collected from Eucranta villosa Malmgren, 1866, Eunone sp., and Gattyana cirrhosa (Pallas, 1766). The material from Eucranta villosa caught at 72.6ºN comprises both a new host record and is the most northerly report of this parasite. Specimens of Eurysilenium which differed from E. truncatum in a number of features were found on Harmothoe fragilis and H. impar (Johnston, 1839). A new family, the Pholoicolidae, is established to accommodate Pholicola chambersae gen. et sp. nov., parasitic on Pholoe pallida Chambers, 1985. The family Phyllodicolidae was represented by all three of its known species: Phyllodicola petiti (Delamare Deboutteville & Laubier, 1960), Cyclorhiza eteonicola Heegaard, 1942 and C. megalova Gotto & Leahy, 1988. The former was found on Eumida ockelmanni Eibye-Jacobsen, 1987, a new host record. A single ovigerous female of C. eteonicola was collected from a new host, Eteone spetsbergensis Malmgren, 1865. Cyclorhiza megalova was common on Eteone longa (Fabricius, 1780) and E. longa/flava complex. A rich diversity of members of the family Saccopsidae was found, including three known species of Melinnacheres M. Sars, 1870 plus nine new species placed in four new genera. Melinnacheres was represented by M. ergasiloides M. Sars, 1870, M. steenstrupi Bresciani & Lützen, 1961 and M. terebellidis Levinsen, 1878. Melinnacheres ergasiloides was found on Melinna elizabethae McIntosh, 1914, M. steenstrupi on members of the Terebellides stroemi-complex and T. atlantis Williams, 1984, while M. terebellidis was found on the T. stroemi-complex and on T. shetlandica Parapar, Moreira & O'Reilly, 2016. A new genus, Trichobranchicola gen. nov., was established to accommodate T. antennatus gen. et sp. nov., a parasite of Trichobranchus sikorskii Leontovich & Jirkov in Jirkov, 2001, T. glacialis Malmgren, 1866 and Trichobranchus sp. The second new genus, Lanassicola gen. nov., was established to accommodate the type species, Lanassicola arcticus gen. et sp. nov. parasitic on Lanassa venusta (Malm, 1874), plus two additional species, L. bilobatus gen. et sp. nov. on Lanassa nordenskjoeldi Malmgren, 1866, and L. dorsilobatus gen. et sp. nov. on Proclea graffii (Langerhans, 1884). A new subfamily, Euchonicolinae, was established within the Saccopsidae to accommodate two new genera, Euchonicola gen. nov. and Euchonicoloides gen. nov. The type species of Euchonicola gen. nov. is E. caudatus gen. et sp. nov., a parasite of Euchone sp., and it includes two other species, E. linearis gen. et sp. nov. on Chone sp., and E. parvus gen. et sp. nov. on Euchone sp. The type species of Euchonicoloides gen. nov. is E. elongatus gen. et sp. nov. found on a host belonging to the genus Euchone, and it also includes Euchonicoloides halli gen. et sp. nov. from Jasmineira caudata Langerhans, 1880. Four species of the family Xenocoelomidae were found: Xenocoeloma alleni (Brumpt, 1897), X. brumpti Caullery & Mesnil, 1915, X. orbicularis sp. nov. and Aphanodomus terebellae (Levinsen, 1878). Xenocoeloma alleni was found on four different species of Polycirrus and on Amaeana trilobata (M. Sars, 1863) and X. brumpti was found on Polycirrus norvegicus Wollebaek, 1912. Xenocoeloma orbicularis sp. nov. occurred only on Paramphitrite birulai (Ssolowiew, 1899). Aphanodomus terebellae was found on three hosts, only one of which, Leaena abranchiata was new.